Anticipatory breach of contract and the necessity of adequate assurance under English law and Uniform Commercial Code - Beheshti, Reza (Informa Law, 2018)
The doctrine of anticipatory breach of contract originated in English law and was adopted into the Uniform Commercial Code. The doctrine remained intact and rigid in English law but certain rules were modified in the UCC regime, which supplemented it by introducing the novel doctrine of adequate assurance, which is absent from English law. This article explores whether English law should undergo a legislative reform to introduce the doctrine of adequate assurance. One hypothesis that will be examined is that adequate assurance is a logical corollary to the doctrine of anticipatory breach of contract, being necessary to secure the full benefit of the latter. The decision in The Pro Victor is investigated: a party made a request for confirmation of performance and the other party’s failure to provide constituted a renunciation—perhaps the first recognition by an English court of the adequate assurance doctrine. Doctrines in English law that may have similar functions to adequate assurance (eg, stoppage in transit, which carries with it a modification of contract and exerts pressure on the insolvent buyer to assure the seller about his performance) are examined in order to assess whether adequate assurance fits well into English commercial law. It is suggested that the doctrine of adequate assurance should formally be introduced as a new section in the Sale of Goods Act 1979.